2013
DOI: 10.1088/0004-637x/765/1/60
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Phase Chemical Model of Hot Cores: The Formation of Glycine

Abstract: A new chemical model is presented that simulates fully coupled gas-phase, grain-surface, and bulk-ice chemistry in hot cores. Glycine (NH 2 CH 2 COOH), the simplest amino acid, and related molecules such as glycinal, propionic acid, and propanal, are included in the chemical network. Glycine is found to form in moderate abundance within and upon dust-grain ices via three radical-addition mechanisms, with no single mechanism strongly dominant. Glycine production in the ice occurs over temperatures ∼40-120 K. Pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
714
6
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 412 publications
(747 citation statements)
references
References 72 publications
(108 reference statements)
23
714
6
4
Order By: Relevance
“…This has been explored extensively in chemical models of hot cores. For example, CH 3 CN can form on grains via CH 3 + CN at ∼30 K. It can also form from HCN in the gas-phase, when HCN evaporates at ∼40 K, through CH + 3 + HCN association followed by a recombination reaction 14 . This gas-phase CH 3 CN re-accretes onto the grains, and can then thermally evaporate around 90 K.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been explored extensively in chemical models of hot cores. For example, CH 3 CN can form on grains via CH 3 + CN at ∼30 K. It can also form from HCN in the gas-phase, when HCN evaporates at ∼40 K, through CH + 3 + HCN association followed by a recombination reaction 14 . This gas-phase CH 3 CN re-accretes onto the grains, and can then thermally evaporate around 90 K.…”
Section: Discussionmentioning
confidence: 99%
“…2 × 10 5 years for warm-up to 200 K) 14 . For CH 3 CN/CH 3 OH, the theoretical abundance ratio increase of two orders of magnitude with temperature up to 100 K agrees well with observations.…”
Section: Discussionmentioning
confidence: 99%
“…12,15 The use of two ultra-high vacuum (UHV) systems allows for complementary studies of selected interstellar relevant surface reactions. Therefore, a combination of experiments performed in these setups gives information on surface reactions occurring at different surface coverages (sub-monolayer vs. multilayer regime), on different substrates (gold, silicates, graphite, and ASW ice), and in different matrix environments (pure NO and NO 2 , NO in polar ice, and NO and NO 2 in apolar ice).…”
Section: Methodsmentioning
confidence: 99%
“…The cumulative outcome of recent observations, laboratory studies, and astrochemical models indicates that there is a strong interplay between the gas and the solid phase throughout the formation process of molecules in space. 1,2 Surface reaction mechanisms on cold dust grains initiate molecular chemistry starting with the formation of H 2 , and dominate the formation of complex organic molecules (COMs) in space. Indeed, interstellar grains provide surfaces on which gas-phase species can accrete, meet, and react, and to which they can donate the excess energy.…”
Section: Introductionmentioning
confidence: 99%
“…Although non-energetic surface reaction pathways leading to the formation of the more complex species studied in this work have not yet been investigated in the laboratory, several models indicate that those species should be formed in the solid phase and could participate in the formation of even more complex species. 11 For instance, Bisschop et al 52 studied the surface hydrogenation of acetaldehyde and found that it converts to ethanol (C 2 H 5 OH) or to CH 4 , H 2 CO, and CH 3 OH.…”
Section: Astrophysical Implicationsmentioning
confidence: 99%